CELL THERAPY OF EPILEPSIA. CLINICAL AND IMMUNOLOGICAL ASPECTS - T. V. Dokukina; M. P. Potapnev; S. M. Kosmacheva; F. P. Hlebokazov; E. L. Slobina; T. S. Golubeva; N. N. Misjuk; M. V. Mahrov; I. V. Shamruk; P. P. Korolevich; A. I. Martynenko; I. V. Bychenko; et al. (Эпилепсия и пароксизмальные состояния)
The aim is to develop and implement a method for the treatment of drug-resistant epilepsy using autologous mesenchymal stem cells and the neuroimaging, immunological and neurophysiological predictors of the brain function.Material and Methods. Twenty patients (12 males and 8 females) with symptomatic drug-resistant epilepsy participated in the study. The patient age varied from 23 to 46 years; and the duration of epilepsy was 7-29 years. Autologous mesenchymal stem cells of the bone marrow were characterized using cultural, morphological, immunological, molecular-genetic, clinical-functional, laboratory, pathopsychological, and neurophysiological methods. The standard parametric and nonparametric statistical tests were used to evaluate the results.Results. The study resulted in producing of cultured autologous mesenchymal stem cells of the bone marrow (AMSCBM) sufficient to conduct 20 courses of cell therapy. In total, 40 transplantation procedures using AMSCBM were performed (20 intravenous and 20 endolumbar injections). Cellularity index in the intravenous inoculate ranged from 39.5 to 110.0 million and that for the endolumbar injection – from 5.1 to 10.0 million with viability not less than 95%. The distribution of AMSCBM by key surface markers (CD105+, CD90+, CD45-, CD34-) matched the criteria of the International Association for cell therapy (ISCT). The cell injections were well tolerated and did not cause any severe adverse effects. To monitor the process of neurogenic differentiation, the expression of the surface markers was determined. In most samples with confirmed neural differentiation, a significant increase in the expression of neuron-specific enolase, nestin and MAR-2 was detected. In patients with symptomatic epilepsy, the most significant deviations from normal values were found for the numbers of cytotoxic and activated cells, natural killer (NK) cells, and T-cells with the NK activity. After a course of cell therapy, a significant decrease in CD4+CD8+, CD3+CD8+, CD3+CD95+, and CD8+CD25+ cells was noted. Also decreased were the numbers of NK cells and T-cells with the NK activity, however, their levels remained relatively high as compared with the control group. Following the treatment, we continued to monitor the patients for 3, 6, and 12 months after the cell administration as well as the patients from the group of comparison.Conclusion. For the first time in the Republic of Belarus, cell therapy in patients with epilepsy was conducted. An intravenous injection of AMSCBM and endolumbar administration of neuro-induced AMSCBM can serve an effective additional therapy of choice in patients with drug-resistant epilepsy.